Qualidade hidroambiental de nascentes no Assentamento Florestan Fernandes, Sul do Espírito Santo - Oliveira, Francielle Rodrigues de (2018)
Water is indispensable for the maintenance of life on the planet. Their availability within the appropriate quality standards for human consumption is fundamental, since it directly influences the health and the quality of life of the population. The Florestan Fernandes Settlement (AFF) does not have a potable water supply network and the springs represent the main source to meet the water demands of the settled families. However, in the recent past, the native forests of the AFF areas have been suppressed for crop and livestock implantation, leaving most of the springs without the permanent protection area and without the minimum recommended protection.These practices endanger the conservation and perenniality of the springs, and may compromise the potability of water. Therefore, the general objective of this study was to evaluate the water quality of springs with different uses in the Settlement Florestan Fernandes, Guaçuí/ES. In order to do so, eight springs were selected, five of which were fenced and planted with seedlings and another three that remain unprotected. Periodic collections and laboratory analyzes to evaluate the physical, chemical and microbiological parameters of the water were carried out to ascertain the characteristics related to the quality as well as the water quality index (IQA) of the springs. In addition, the Nascent Environmental Impact Index (IIAN) was calculated in order to visually identify the quality and degree of impact in the contribution area of each spring. Finally, a questionnaire was applied to the residents to construct a socioenvironmental diagnosis of settled families. The IIAN showed that 25% of the springs were classified as "good", 37.5% as "reasonable”, another 25% classified as" bad" and 12.5% as "terrible". No spring had its degree of conservation classified as "great". From the results of water quality parameters, it was concluded that there is non-conformity with the ordinance 2914/11 of the Ministry of Health and CONAMA Resolution 357/05 and therefore, the springs are fit for human consumption only after previous disinfection. The IQA proposed by CETESB classified seven springs with good quality and one with reasonable quality. It was verified that lack of basic sanitation infrastructures and hygienic-sanitary practices, together with the lack of environmental planning and management strategies, results in an absence of adequate management of land use and occupation and consequently of the water quality.